THE USE OF GRAPHIC NOVELS AS LITERARY TEXT IN LITERATURE CLASS - Subhan, Yan Ardian; Baroroh, Aisyah Al-; Hani, Umi (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2023)
Learning requires text as material for teaching. In literature class, literary text play important roles as the material to deliver the lessons. Many literature classes use common literary texts such as short story, novel, poems, or drama script as the material but nowadays graphic novel provides alternative material for teaching literature. Graphic novel is a type of contemporary novel that uses graphic elements in its narrative storytelling. The use of graphic novels in teaching and literary analysis has begun to be widely used in the classroom; therefore, the aim of this study is to portray the use of graphic novels in literature classes. This study focused on how students accept graphic novels use as material in literary classes. Qualitative study was used in this study and data were gathered from students by using questionnaires. Data were taken from 7th semester students English Department, Faculty of Letters - Universitas Pamulang and were analyzed descriptively. The result of this study showed that students accept the use of graphic novels and help to get a better understanding of the use of the graphic novel as material for literature classes. Keywords : Graphic novels; literary text; literary material; literature learning; students’ acceptance